2007 IEEE Electric Ship Technologies Symposium 2007
DOI: 10.1109/ests.2007.372116
|View full text |Cite
|
Sign up to set email alerts
|

A PC-Cluster Based Real-Time Simulator for All-Electric Ship Integrated Power Systems Analysis and Optimization

Abstract: This paper presents the development of a PC-cluster based real-time simulator for All Electric Ship (AES) Integrated Power System (IPS) analysis and optimization. The system is established at the University of Michigan with the financial support from the U.S. Office of Naval Research (ONR). It is aimed to address the multi-disciplinary issues associated with the allelectric ship, such as optimal power management and dynamic system reconfiguration. In parallel with hardware construction, a modularized IPS model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In equation 12, the total power delivered by the i-th diesel generator at the j-th time step is defined as the sum of the power delivered by all the n-th power ranges P g enij n , defined by the piecewise linear function. Further, in (13) the power limits of each step of the function are defined as P nomn and equation (14) states that it is not possible to work in the (n+1)-th step without working also in the previous n-th step. Finally, the corresponding penalty value is proposed in (15), where P g % is the ratio between P g enij n and the product of z i j n and P nomn .…”
Section: B Power Generation System Ems Algorithmmentioning
confidence: 99%
“…In equation 12, the total power delivered by the i-th diesel generator at the j-th time step is defined as the sum of the power delivered by all the n-th power ranges P g enij n , defined by the piecewise linear function. Further, in (13) the power limits of each step of the function are defined as P nomn and equation (14) states that it is not possible to work in the (n+1)-th step without working also in the previous n-th step. Finally, the corresponding penalty value is proposed in (15), where P g % is the ratio between P g enij n and the product of z i j n and P nomn .…”
Section: B Power Generation System Ems Algorithmmentioning
confidence: 99%
“…The majority of the simulator’s codes belong to the generator, grid, governor, and turbine. Unlike many other studies which used prepared models in costly commercial software, 5 in this work, as was stated in modeling section, the mathematical model of these mechanical and electrical parts has been implemented in LabVIEW. Their parameters were also used to examine different scenarios during tests.…”
Section: Hil Simulator Architecturementioning
confidence: 99%
“…There are many vendors worldwide that are providing hardware-in-loop (HIL) simulators with different RT engines. 1 These real-time engines often vary from digital signal processors, 2,3 personal computer (PC)-based clusters, 4,5 field-programmable gate array (FPGA) coprocessor boards, 6 or simple PC-based DOS targets. 7 Although it was assumed that these targets are normally limited to small plants, recent hardware developments and examination of those platforms have shown that PC-based RT kernels with properly tuned priority levels enable a good level of reliability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when combining renewable energy technologies such as wind energy [1] and photovoltaic energy [2] with traditional power generation technologies, it can provide low cost and highly reliable power solutions for island and remote area applications. Meanwhile, state-of-the-art fuel cell technologies bring in the low emission and high efficiency option of power generation, making them very attractive for automotive powertrain [3] and shipboard power systems [4]. In general, hybrid power systems can be categorized into AC Hybrid Power Systems (AHPS) and DC Hybrid Power Systems (DHPS), depending on the types of power bus used.…”
Section: Introductionmentioning
confidence: 99%